Design and fabrication of fixed bed pyrolysis reactor using scrap tire for pyrolysis oil production - Aziz, M.A.; Rashid, Muhammad Mahbubur; Islam, M.R. (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2017)
In this research, a design and construction of fixed bed pyrolysis reactor and solid waste tire for pyrolysis oil production have been completed and the characteristics of the pyrolysis oil have already been checked and compared to the other research experimental results. A fixed bed reactor, reactor shield, solid horizontal condenser, oil or gas burner for furnace heating and the reactor shield has been designed properly for accurate experimental operation. This fixed bed batch type pyrolysis reactor method will demonstrate the energy saving concept of solid waste tires by creating energy stability of the present world. From this experiment prod-uct yields (weight %) for liquid or pyrolytic oil (wt. %) 34 %, char (wt. %) 57 %, gas (wt. %) 9%.